Implementasi Sistem Informasi Pengelolaan Surat Jalan dan Invoice Menggunakan Framework CodeIgniter - Beny Rahman Hakim (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The development of information technology has become a primary pillar in enhancing corporate operational efficiency, where rapid and accurate data integration significantly determines business competitiveness. Case study in PT Gawi Anjung Bersama (GAB) revealed that the company is facing operational constraints because the management of delivery orders and invoices still relies on conventional office applications such as Microsoft Excel and Word. This procedure causes hurdles in data sharing among staff and results in low information security due to the absence of integrated access control settings. This research aims to design and develop the Gawi Anjung Bersama Information System (SIGAB), a web-based system implementing the CodeIgniter framework. The system is developed using Waterfall model, encompassing stages from analysis, design, and implementation to testing. The research flow starts with problem identification, primary and secondary data collection, and functional and non-functional requirements analysis. The system is designed using Unified Modeling Language (UML) modeling, specifically Use Case and Class Diagrams, as well as Entity Relationship Diagrams (ERD) for the database. The system interface is designed as wireframes on Figma web. This system separates access rights into three main actors namely owner, administrator, and staff, to ensure data security. Blackbox testing results, conducted after the system was hosted, indicate that all functional features operate as intended. The implementation of SIGAB is expected to optimize the management of delivery orders and invoices at PT GAB.